Effects of Aluminum Powder on Ignition Performance of RDX, HMX, and CL-20 Explosives. (17th January 2018) - Mao, Xiaoxiang; Jiang, Longfei; Zhu, Chenguang; Wang, Xiaoming
Abstract : As a kind of high explosives, aluminized explosive cannot release the energy maximumly, which is a key problem. Using DTA-TG equipment, the ignition performance of three kinds of aluminized explosives (RDX, HMX, and CL-20) with different mass percentages of aluminum powder (0%, 10 wt.%, 20 wt.%, and 30 wt.%) was investigated. The results showed that the energy release of the HMX/Al composite explosive with 10 wt.%, 20 wt.%, and 30 wt.% aluminum powder was only equivalent to 80%, 65%, and 36% of pure HMX, respectively. It was similar to RDX/Al and CL-20/Al composite explosives, except the CL-20/Al mixture with 10% aluminum powder. Rather than participating in the ignition and combustion, the aluminum powder does effect the complete reaction of RDX, HMX, and CL-20 in the initial stage of ignition or in the lower temperature area of the boundary.